Jaw stiffness and dental extractions due to pharmacodynamic interaction between mirtazapine and chlorpromazine - MASTROIANNI, Patricia de Carvalho; VARALLO, Fabiana Rossi; MACHUCA, Manuel (Vitae, 2014)
A comprehensive assessment of the patient’s drug related needs allows identifying health problems drug-induced. It has been demonstrated that each dollar spent on clinical pharmacy services reduces the pooled median cost of health by 4.81 dollars. Jaw stiffness (bruxism) can be a serotonergic manifestation related to drugs with serotonin reuptake inhibition activity. Clinical manifestations also include: agitation, tachycardia, high blood pressure, tremor, fever, dyspnea, diarrhea, mental confusion and insomnia.